Kesadaran Metakognitif Mahasiswa pada Perkuliahan Sistem pada Hewan dengan Penugasan Berbasis Portofolio dan Jurnal Belajar - Jariyah, Ita Ainun; Ummah, Khoirotul (Bioscientist : Jurnal Ilmiah Biologi, 2022)
The rapid development of the digitalization era needs to be improved by problem-solving abilities in every challenge. One of the competencies that support problem-solving abilities is metacognitive strategies ability. Metacognitive awareness is an important competency in learning that must be mastered by students to be able to understand and control the knowledge they acquire. This research is a descriptive study to determine the proportion of students’ metacognitive awareness in the lecture system on animals with portfolio-based assignments and learning journals. The results of the metacognitive analysis of awareness are used as a follow-up design for the next lecture to increase students’ metacognitive awareness. Metacognitive awareness data is measured by metacognitive awareness which includes aspects of declarative knowledge, procedural knowledge, and conditional knowledge. The results showed that the students’ metacognitive awareness was mostly in the medium category 66.67%, the rest in the low category 19.04%, and the high category 14.29%. These results indicate that students’ metacognitive awareness still needs to be improved by making improvements in the next lecture process.